MODEL RANGSANG TANGGAPAN KONSUMEN MAHASISWA DI BENGKALIS - Yunelly Asra (Politeknik Negeri Bengkalis, 2015)
Absract :This study aims to determine the model of marketing stimuli for consumers teenagers, especially students in Bengkalis by the response they give the market encouragement that they received. Data collected in a non-probability sampling of 245 respondents with methods survey. Data collected through questionnaires with observational techniques. The results showed that the tendency of the responses given to the marketing stimuli is low. This is caused they are already accustomed to stimuli that exist today , they will be difficult to accept when there are new stimuli. Keywords: Marketing Stimuli, Consumer Response